2012
DOI: 10.1111/j.1471-6712.2012.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, completeness and comprehensiveness of information on pressure ulcers recorded in the patient record

Abstract: The purpose of documentation to record, communicate and support the flow of information in the patient record was not met. The patient records lacked accuracy, completeness and comprehensiveness, which can jeopardise patient safety, continuity and quality of care. The information on pressure ulcers in patient records was found not to be a reliable source for the evaluation of quality in health care. To improve accuracy, completeness and comprehensiveness of data in the patient record, a systematic risk assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
0
23
0
4
Order By: Relevance
“…The scarce existing literature focuses on pressure ulcers as the only studied AE, revealing that the documented information on AEs is not accurate and incomplete (17)(18) .…”
Section: Introductionmentioning
confidence: 99%
“…The scarce existing literature focuses on pressure ulcers as the only studied AE, revealing that the documented information on AEs is not accurate and incomplete (17)(18) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, coding standards typically require a documented physician diagnosis in order to be coded in administrative data. There is evidence that physician documentation about some types of adverse events (eg, pressure ulcers) is poor 45,46. This limitation became apparent during our validation study, as there were insufficient cases of pressure ulcers and fall-related injuries identified during 1 fiscal year.…”
Section: Discussionmentioning
confidence: 96%
“…15 No que se refere aos registros, pesquisas [16][17][18] mostram que é preciso melhorar a precisão e a abrangência nos registros.…”
Section: Discussionunclassified